Phenotypic Differentiation of Ecologically Significant Brachidontes Species Co-Occurring in Intertidal Mussel Beds from the Southwestern Atlantic - Adami, Mariana Laura (2013)
Intertidal communities from rocky shores of the southwestern Atlantic are dominated by two small-sized mussels of the genus Brachidontes, B. rodriguezii (d’Orbigny, 1846) and B. purpuratus (Lamarck, 1819). Their generic placement, separation of specimens based on external conchological characters and geographic distribution are problematic. We conducted a comparative study based on extensive collections and observations at 14 sites along the coasts of the southwestern Atlantic, complemented by the study of materials from museum collections. Well-preserved specimens of the two species are distinguishable on the basis of shell characters, some of them previously ignored, over their combined latitudinal range.